Experience of Using Tocilizumab in a Patient with Polyarticular Juvenile Rheumatoid Arthritis with Cervical Spine Lesions - E. A. Ligostaeva; N. A. Curikova; E. I. Alekseeva; S. E. Valieva; T. M. Bzarova; T. V. Sleptsova (Union of pediatricians of Russia, 2015)
The article describes a case of polyarticular juvenile idiopathic arthritis lesions of the cervical spine. This clinical example demonstrates the high efficiency of tocilizumab in a patient with polyarticular juvenile idiopathic arthritis with lesions of the cervical spine. After the first injection of tocilizumab a decrease in the following was observed: pain in the cervical spine and affected joints, severity of functional disorders in the temporomandibular joint and the interphalangeal joints, cervical spine; a 30% improvement in the JADAS, ACRpedi30 was achieved. By the 8th week of therapy the proliferative changes in the joints of the hands and arthralgia decreased, as well as the duration of morning stiffness. After 3 months there was a decrease in the activity of Jia (DAS28), and the erythrocyte sedimentation rate and serum concentrations of C-reactive protein. Adverse effects during therapy with tocilizumab were not observed. The disease activity decreased, (assessed using the visual analog scale (VAS)), as well as the functional impairment (assessed using the Children Health Assessment Questionnaire (CHAQ)). The emotional status and quality of life of the child and her family improved significantly.